Mathematical Modelling of Wave Impact on Floating Breakwater - Fadhlyya Arawaney, Abdul Ghani; Mohd Shahridwan, Ramli; Nor Aida Zuraimi, Md Noar; Abdul Rahman, Mohd Kasim; Greenhow, Martin (IOP Publishing, 2017)
The impact of breaking wave on shoreline can be lessen or prevented by placing some kind of protection before the wave to reduce the speed of the wave before attacking the shoreline. Such protection can be in the form of a breakwater which is a structure designed to help reducing the wave intensity in whether in inshore waters or relatively shallow water. Thus, a mathematical model of Pressure Impulse, P is used to model the effect of waves exerted on a wall of a breakwater. A two-dimensional field of equations is derived for P which are applicable in three regions of breakwater problems by expressing this in terms of eigenfunctions that satisfy the boundary conditions apart from that the impact region and the matching of the three regions (before the breakwater, under the breakwater and after the breakwater). As in Cooker, we found that the equations of P in region 1 and region 3 are same as Cooker only that equation in region 3 has to include a secular term.